PENGARUH BRAIN GYM TERHADAP KONSENTRASI ANAK USIA PRASEKOLAH DI KB AS SIDIQ - Febriyanti, Siti Nur Umariyah; Wahyuningsih, Riska; Widiyaningsih, Widiyaningsih (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Abstract Background : Learning concentration is a factor that determines a person's success whether studying in class, study groups or studying independently. The low concentration of a person in learning will cause a decrease in one's learning outcomes. There are several methods that can be used to increase concentration in children. One of them is Brain gym. Brain gym was chosen as one of the methods to increase concentration. Research Objectives : To analyze the effect of Brain Gym on the concentration of pre-school children in As-Sidiq Playgroup. Research Methods: this type of quantitative research is quasi-experimental. The research design used Pre and Posttest one group design. Total 19 respondents. The research instrument used was the Wechsler Preschool and Primary Scale of Intelligence (WPPSI) observation sheet. The results: The results of the statistical test using Wilcoxon (P-value = 0.000 0.05) means that there is an effect of Brain Gym (brain exercise) on concentration in children preschool age at As Sidiq Playgroup. Conclusion : Brain Gym (brain exercise) can improve concentration in preschool age children at As Sidiq Playgroup. Keywords: Preschool Children, Brain Gym, Children Concentration